Analysis of Designed Flood Discharge Using the Nakayasu HSS Method on the Alo River, Sidoarjo - Dinan Dana; Novie Handajani (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
The design flood discharge is an important parameter in hydrological analysis used as a basis for flood control structure planning and water resources management. This study aims to determine the design flood discharge in the Alo Watershed through analysis of areal rainfall, design rainfall, effective rainfall, and the Nakayasu Synthetic Unit Hydrograph (HSS). Areal rainfall was calculated using the Thiessen Polygon method based on rainfall data from seven rainfall stations, namely Gedangrowo, Kludan, Putat, Kedungcangkring, Porong, Krembung, and Budugbulus during the observation period of 2016–2025. The design rainfall was analyzed using the Log Pearson Type III Distribution and tested using the Chi-Square and Smirnov-Kolmogorov methods at a significance level of 5%. Furthermore, the design rainfall was converted into a 6-hour hourly rainfall distribution using the Mononobe Method, then calculated as effective rainfall with a runoff coefficient of 0.204. The effective rainfall distribution is used as input in the formation of flood hydrographs using the Nakayasu Synthetic Unit Hydrograph (HSS) Method. The results of the study indicate that the Log Pearson Type III Distribution meets the distribution suitability test so it is suitable for use in the analysis of planned rainfall in the Alo Watershed. The Nakayasu HSS analysis shows that the peak flood discharge occurs at the 2nd hour for all return periods and increases as the return period increases. The Design Flood Discharge obtained for return periods of 2, 5, 10, 25, and 50 years is 63.933 m³/s, 72.446 m³/s, 77.339 m³/s, 82.922 m³/s, and 86.742 m³/s, respectively. The results of this study can be used as a basis for planning flood control structures and water resource management in the Alo Watershed. Contribution to Sustainable Development Goals (SDGs):SDG 6: Clean Water and SanitationSDG 9: Industry, Innovation, and InfrastructureSDG 11: Sustainable Cities and CommunitiesSDG 13: Climate ActionSDG 15: Life on Land